Percutaneous Sclerotherapy with Bleomycin for Orbital Lymphangioma: A Case Report: Doi: 10.36351/pjo.v41i4.2128 - Tanveer, Tehreem; Ahmad, Saadullah; Tahir, Faizan; Akram, Fatima (Pakistan Journal of Ophthalmology, 2025)
Lymphangiomas, or lymphatic malformations, are benign, multi-cystic, hamartomas which are localized vascular malformations believed to arise during embryonic period.1 Lymphatic malformations most frequently occur in pediatric populations in the region of head and neck and they account for about 25% of benign pediatric vascular tumors and about 4% of all vascular tumors.1 Orbital lymphangiomas have a prevalence of 1.1 to 5.3 cases per 10,000 live births and are equally common in both males and females.2Histopathologically, lymphangiomas consist of endothelium lined, thin-walled dilated lymphatic spaces, filled with eosinophilic proteinaceous material.1Management of lymphangiomas is challenging. We report a case of a 9-year-old female who had orbital lymphangioma and was treated with sclerotherapy. Outcomes of treatment and review of literature is presented here.